Effect of hospital safety net designation on treatment use and survival in hepatocellular carcinoma. Issue 4 (26th October 2017) - Mokdad, Ali A.; Murphy, Caitlin C.; Pruitt, Sandi L.; Mansour, John C.; Marrero, Jorge A.; Singal, Amit G.; Yopp, Adam C.
Abstract : BACKGROUND: Racial/ethnic minorities with hepatocellular carcinoma (HCC) have worse survival than non‐Hispanic whites. Comparing patient outcomes across health care delivery systems can identify biological and care delivery mechanisms contributing to this disparity. We compared presentation, treatment, and survival of HCC patients treated at safety net hospitals (SNHs) and non‐SNHs. METHODS: Patients diagnosed with HCC from 2001 to 2012 were identified in the Texas Cancer Registry. We compared hospital and patient characteristics across three hospital categories: non‐SNHs, low‐proportion SNHs (l‐SNHs), and high‐proportion SNHs (h‐SNHs). Covariate‐adjusted treatment use and overall survival were compared among the 3 hospital categories. RESULTS: Despite comprising only 23% of hospitals, h‐SNHs cared for 42% of 17, 489 HCC patients and disproportionately delivered care to racial/ethnic minorities and patients of low socioeconomic status compared with non‐SNHs. Compared with non‐SNHs, treatment use was similar at l‐SNHs (45% vs 45%; adjusted odds ratio [OR], 0.97; 95% confidence interval [CI], 0.89‐1.06) but significantly lower at h‐SNHs (32% vs 45%; OR, 0.64; 95% CI, 0.57‐0.73). Similarly, patients with localized HCC were less likely to undergo curative treatment at h‐SNHs than non‐SNHs (OR, 0.51; 95% CI, 0.40‐0.66). Compared with non‐SNHs, overall survival was similar at l‐SNHs (hazard ratio [HR], 0.93; 95% CI, 0.89‐0.98) but significantly worse at h‐SNHs (HR, 1.30; 95% CI, 1.22‐1.39). CONCLUSION: Patients at SNHs are less likely to undergo HCC treatment, even when diagnosed at an early stage, which likely contributes to worse survival. System‐level differences in care delivery may partly explain racial/ethnic and socioeconomic disparities in HCC prognosis. Cancer 2018;124:743‐51. © 2017 American Cancer Society . Abstract : Amid ongoing national health care reform in the United States, safety net hospitals (SNHs) play an increasingly integral role in caring for vulnerable hepatocellular carcinoma (HCC) patients. SNHs disproportionately care for racial/ethnic minorities and socioeconomically disadvantaged HCC patients; however, HCC patients at SNHs are significantly less likely to undergo HCC‐directed treatment, which contributes to worse overall survival.